Student Learning Motivation in Physical Education Learning Based on Physical Activity: A High School Analysis Study - Dimas Duta Putra Utama; Muchsin Doewes; Febriani Fajar Ekawati; Zsolt Németh (Universitas Nahdlatul Ulama Cirebon, 2023)
Study Purpose. Articulate the key intersection points and differences between motivational indicators that can influence the occurrence of motivation to learn in physical education learning at school. This study was designed to examine the effect of physical activity participation in organized schools on indicators of learning motivation in physical education learning. Materials and methods. Assessment of physical activity based on a questionnaire using the International Physical Activity Questionnaire (IPAQ) and motivation to learn physical education based on research on six indicators that have passed the Expert Judgment stage. Participants consisted of 202 grade 10 students who attended physical education classes at SMAN 1 Sukoharjo, Central Java. The greater the effect of physical activity on participating students to increase the overall learning motivation is higher. Perceptions of learning motivation indicators related to physical activity items. Results. In both of these influence assessments, indicators of learning motivation can be said to be influenced by several physical activity items. Changes in physical activity can predict changes in learning motivation, except for Learning Tools and Teaching Methods. In particular, physical activity items can affect indicators of students' environmental conditions. Conclusion. There is a dynamic influence between the participation of learning motivation indicators in physical education learning on student activities at school.